The effect of WC addition on CrMnFeCoNi high entropy alloys: crystal-micro structure, hardness and wear behavior - Tasgin, Yahya; Kanca, M. Sait; Kok, Mediha; Anik, Kerem (Iop Publishing Ltd, 2025)
High entropy alloys are produced by combining four or more elements in close percentage ratios. Recently, these alloys have become the preferred group due to their superior mechanical and thermal properties. In this study, tungsten carbide (WC) was doped into CrMnFeCoNi alloys at different ratios, and the effects of WC and heat treatment on the doped alloys were investigated. XRD, SEM, and EDS analyses, wear tests, and microhardness measurements were performed on the produced samples to examine their microstructural properties. When comparing the heat-treated samples with WC (3%, 5%, and 10% additions) to the untreated samples, it was found that the average hardness values of the heat-treated samples were higher. Although the grain structures of the samples, as observed through XRD, SEM, and EDS, were preserved, their ratios were altered, and the wear tests revealed that the mass losses of the heat-treated samples increased.
Keywords: tungsten carbide; high entropy alloy; crystal structure; wear test